Survey data on the costs and benefits of livestock management practices in the lowlands of Ethiopia - Karanja Ng'ang'a, Stanley; Anyango Jalang'o, Dorcas; Mwungu, Chris Miyinzi; Nguru, Wilson Maina; Girvetz, Evan Hartunian; Smith, Gordon; Alemayehu, Sintayehu (International Center for Tropical Agriculture, 2019)
The survey data on costs-benefit analysis of livestock management practices in the lowlands of Ethiopia is systematically organized in Microsoft Excel tables. Each of the three land management practices, that is, rangeland improved, restoration of degraded land, and fodder cropping and poultry expansion have data contained in excel tables. The data entails general household characteristics, the region where the practices are common and activities households indulged in before and after introduction of land management practices. The data also contains costs of inputs and labour required for the land management practices; mainly for implementation, maintenance and operation. Additionally, the tables include data on products generated from the land management practices as well as their market prices.